Design and Development of Wearable Sensor System using MQTT Protocol for Real Time Kinematics Analysis - Rana, Manju; Mittal, Vikas (2019 Global Conference for Advancement in Technology (GCAT), 2019)
Wearable sensors data fusion is the most advanced and robust technology to study the motion of a body and perform kinematics analysis in real time. The main application of such sensor systems is in sports training and performance measurement. Advancements in wearable technology permit continuous observation and analysis of the sports person without causing any discomfort during training sessions. Multiple sensors are required to be mounted on the subject and synchronous data is needed from all the sensors to get a complete picture of the athlete's performance.The presented design of wearable sensor system involves a wireless sensor network of smart Inertial Measurement Units and implementation of MQTT Protocol for communication. Pi Zero W has been installed with Mosquitto broker. The transmitted data is published in real time on two different MQTT clients - open source software MQTT SPY and a custom android mobile app. This data can be further stored in a data-base to explore various data fusion algorithms or techniques for kinematics analysis of the subject.